Pendampingan Kesadaran Lingkungan sebagai Implementasi Pendidikan Karakter Peduli Lingkungan di SD Negeri 2 Ngrogung - Yiyik Nurdiana; Tri Prasetyo Utomo (Social Science Academic, 2025)
Environmental awareness is a crucial aspect in development students’ character from an early age. This study aims to describe the implementation of elementary school environmental care character education at SD Negeri 2 Ngrogung. Using a qualitative descriptive approach, document and information were collected through observation, interviews, and documentation. The findings reveal that environmental care character education is implemented through routine habituation programs such as Jumat Bersih (Friday Reset), school waste bank management, school garden maintenance, and the integration of environmental values into classroom learning. The implementation is supported by the commitment of the school principal, active teacher participation, and student involvement, while inhibiting factors include limited facilities and the inconsistent awareness of some students. Overall, environmental care character education has been proven to foster students’ ecological awareness and responsibility, although its effectiveness still requires reinforcement through adequate facilities and stronger collaboration among schools, families, and communities.